Pengaruh Kualitas Pelayanan dan Kepuasan Terhadap Loyalitas Eksportir Jasa Freight Forwading pada PT. Oriental Logistik Indonesia - Miftahul Khasanah; Muhammad Akbar (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The purpose of this study was to analyze (1) the effect of quality on Exporter Loyalty (2) the effect of satisfaction on Exporter Loyalty (3) the effect of Quality and Satisfaction on Exporter Loyalty. The type of research used was quantitative because it emphasizes testing theories through measuring research variables with numbers and analyzing data using statistical procedures. The population in this study were customers who used freight forwarding services, with a sample selection of 47 people. From the results of the study, it can be concluded that there is an effect of quality variable on Exporter Loyalty, thus if the quality is improved, there will be an increase in Exporter Loyalty in freight forwarding services at PT. Oriental Logistik Indonesia. There is also a significant effect of the satisfaction variable on Exporter Loyalty. The effect of the two variables can be said to be significant. This happens because there is an effect of quality and satisfaction on the loyalty of exporters of Freight forwarding services at PT.Oriental Logistik Indonesia.